2016
DOI: 10.1080/21645515.2015.1119345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of host genetic polymorphisms on vaccine induced antibody response

Abstract: Many host-and vaccine-specific factors modulate an antibody response. Host genetic polymorphisms, in particular, modulate the immune response in multiple ways on different scales. This review article describes how information on host genetic polymorphisms and corresponding immune cascades may be used to generate personalized vaccine strategies to optimize the antibody response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 103 publications
(104 reference statements)
1
39
0
Order By: Relevance
“…Patients with infectious diseases often show heterogeneous clinical courses with a range of associated morbidities and variable mortality. This is dependent on a series of factors covering the complex aspects of host-pathogen interactions (1)(2)(3)(4)(5). IFNs play a crucial role in these interactions-defining the outcome of many viral, bacterial, fungal, and parasitic infections (6-16) (see Figure 1).…”
mentioning
confidence: 99%
“…Patients with infectious diseases often show heterogeneous clinical courses with a range of associated morbidities and variable mortality. This is dependent on a series of factors covering the complex aspects of host-pathogen interactions (1)(2)(3)(4)(5). IFNs play a crucial role in these interactions-defining the outcome of many viral, bacterial, fungal, and parasitic infections (6-16) (see Figure 1).…”
mentioning
confidence: 99%
“…Our pilot study is the first study in children with haemophilia to confirm adequate immunogenic responses to SQ diphtheria and tetanus vaccination. Factors that affect the immune response to vaccine antigens are complex and include host factors like obesity, smoking, genetic polymorphisms as well as vaccine related factors, including site of injection, and whether antigens are given as separate injections or combined with other antigens . In our study, all children received combined vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as previous exposure to IAV infections or vaccines, age, and the closeness of the match between the vaccine and circulating strains are important to explain differences in vaccine effectiveness between seasons and group populations [44,46,[150][151][152]. However, multiple reports have demonstrated that the host genetic background and polymorphisms on key immune response genes modulate the immune response to infection or vaccination [153][154][155][156][157][158][159][160]. Therefore, new insights into IAV-host interaction and immune response modulating factors could allow us to design better vaccination strategies.…”
Section: Snps In Genes That Influence the Iav Vaccine Responsementioning
confidence: 99%
“…SNPs may modify the humoral immune response after IAV vaccination. Therefore, their impact on the immune responses induced after IAV vaccination are being analyzed [153][154][155][156]. The major histocompatibility complex (MHC) is localized in chromosome 6 of the human genome, it includes multiple genes and exhibits considerable diversity between populations.…”
Section: Snps In Genes That Influence the Iav Vaccine Responsementioning
confidence: 99%